Application and concentration selection of dithiothreitol for correcting false elevation of D-dimer - Jia-Wei Zeng; Guang-Hao Song; Mao Xia (Practical Laboratory Medicine)
Background: Immunological methods for D-dimer detection are prone to interference, leading to falsely elevated values. This study evaluates the optimal concentration and corrective efficacy of dithiothreitol (DTT) in addressing false D-dimer elevations. Methods: Plasma samples from seven patients with falsely elevated D-dimer levels, identified using the Sysmex CS5100 coagulation analyzer, were analyzed. Correction was performed using the Stago STA-R Max analyzer with alternative detection antibodies. Additionally, plasma samples from thirty patients with confirmed D-dimer elevations were treated with varying concentrations of DTT (0.01, 0.05, 0.10, and 0.20 mol/L) and normal saline (NS). The optimal concentration of 0.01 mol/L DTT was identified and applied to the experimental group. The results were compared with those obtained using an alternative immunoassay method. Results: In the true elevation group, samples treated with 0.01 mol/L DTT showed no significant difference in D-dimer levels compared to the NS control or original results (all P > 0.05). Higher concentrations of DTT significantly lowered D-dimer levels compared to the NS group (all P < 0.05). In the experimental group, 0.01 mol/L DTT treatment and the alternative immunoassay method similarly reduced D-dimer levels, with no significant difference between the two correction methods (P > 0.05). Conclusion: A 0.01 mol/L DTT solution effectively corrects falsely elevated D-dimer levels without affecting true elevations, yielding results comparable to those achieved by changing the immunoassay method.